2017
DOI: 10.1063/1.5017228
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response and mooring optimization of spar-type substructure under combined action of wind, wave, and current

Abstract: Floating wind turbines (FWTs) have become the preferred structures to exploit offshore winds since a large part of the offshore wind resource is located in deep water zones. In the harsh marine environment, a spar-type substructure is the most promising substructure for FWTs with good structure stability and economic advantages. In this study, the surge, heave, and pitch motions of the spar-type substructure under combined action of wind, wave, and current are analyzed by using the AQWA module of ANSYS. Beside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…8) innovative floater designs may not be technically feasible from a structural integrity and manufacturability point of view, adopting the standard manufacturing solutions. But they would be feasible if considering different structural realization approaches, such as braces and truss structures or tendons, as already used in the oil and gas industry (Chen et al, 2017;Perry et al, 2007;Bangs et al, 2002) or utilized in innovative floater concepts (Fig. 6) (Richard, 2019;Stiesdal, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…8) innovative floater designs may not be technically feasible from a structural integrity and manufacturability point of view, adopting the standard manufacturing solutions. But they would be feasible if considering different structural realization approaches, such as braces and truss structures or tendons, as already used in the oil and gas industry (Chen et al, 2017;Perry et al, 2007;Bangs et al, 2002) or utilized in innovative floater concepts (Fig. 6) (Richard, 2019;Stiesdal, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This, however, leaves open the possibility of subsequent fine tuning of the conceptual design solution obtained through optimization based on hydrodynamic and system-level analyses. By addressing the mooring system in the subsequent detailed design optimization or even in a successive but separate optimization algorithm, the dynamic response of the FOWT system, as well as the mooring line tension itself, can be significantly improved by considering an advanced and more complex optimization problem, in which -apart from various line diameters and lengths -different mooring line arrangements and distribution forms can be utilized, the optimum number of lines within the mooring system and best fairlead position can be elaborated, different mooring types can be used or even mixed within segmented lines, and also clump weights can be incorporated (Tafazzoli et al, 2020;Barbanti et al, 2019;Men et al, 2019;Chen et al, 2017).…”
Section: Floater Structural Massmentioning
confidence: 99%
See 2 more Smart Citations
“…They also found that the viscous damping contributed by the heave plate is a major component of the total damping. Meanwhile, Chen et al [30] presented a spar-type substructure integrated with the heave plates moored by the optimized mooring system. The dynamic response of the platform under different load conditions were performed using AQWA.…”
Section: Introductionmentioning
confidence: 99%